A global perspective on insect-based foods: willingness to eat, brand equity impact, reasons for not eating and consumer acceptability of an insect-based product - Castro Delgado, Mauricio (Kansas State University, 2019)
Insects are becoming more and more popular as a food choice or an ingredient, but the first sensory perception is still triggered by visual cues which influence the overall acceptability of any product. Different studies have suggested to start incorporating insects in familiar food products first and in a powder form to avoid the disgust factor and lower the food neophobia behavior. The first part of this study aims to understand the willingness to eat an insect based products from a global perspective and determine the impact of adding insect powder to specific product of a worldwide brand portfolio. A survey was launched in more than ten countries targeting different regions, backgrounds and cultures. The questionnaire was divided in diverse topics, the reasons for not eating insects segment was the focus of the second part of this research, which explained the main concepts or ideas why consumers would not taste an insect product. Following the outcomes from the unwillingness and reasons to avoid insects, this investigation explored the consumer preferences of a chocolate chip cookie made partially with cricket powder. The results showed that most of the countries were unwilling to try insect products, demonstrating a negative a correlation towards the purchase intention of other products within a brand. The top three barriers that stop consumers to consider eating foods containing insect powder as an ingredient, are led by the appearance factor where no insect fragments should be in the food, then just the concept of consuming insects is disgusting, followed by the statement “Insects are dirty/filthy” were the other two reasons. The sensory properties like taste and texture were not significant limitations to evade insect products. After the consumer acceptability test conducted in USA, Mexico and Spain, the 15% cricket powder chocolate chip cookie was well acceptable and showing higher liking scores than the control cookie in some of the countries. The results showed that adding insects partially in a baked product formula, does not modified the sensory characteristics and the intensity attributes maintained the same pattern as the control sample. The cookie with higher cricket powder percentages was only preferred in Mexico, the USA and Spain participants showed irrelevance (neither like nor dislike) the sample.
Keywords: Sensory science; Insects; Disgust; Food neophobia; Entomophagy; Brand equity